Healthcare needs and experiences of foreign residents in Japan by language fluency. Issue 1 (8th December 2021) - Okamoto, Miyoko; Matsuda, Yui; Foronda, Cynthia L.
Abstract: Objective: Two percent of the Japanese population is comprised of foreign residents with further increase expected due to immigration policy revisions. The purpose of this paper is to examine the healthcare needs and difficulties experienced by foreign residents in Japan by level of their Japanese language fluency. Design: A quantitative, descriptive design was used. Sample: We surveyed foreign residents in the greater Tokyo area ( N = 209). Measurements: The research team created the survey questions and the contents of the survey include foreign residents' experiences during their visits or stays at medical and public health facilities in Japan. Results: More than 90% of the participants or their families visited medical facilities in Japan regardless of Japanese language fluency; however, those with less Japanese language fluency experienced statistically significant uneasiness or inconvenience concerning communication compared to those with native Japanese language fluency ( p = .000). Conclusions: Nurses in Japan may benefit from additional training related to use of interpreters as well as education about diversity and cultural humility. Through better understanding of the specific communication barriers of foreign residents, nurses will be able to better anticipate difficulties and address them.